Chinmedomics: A Powerful Approach Integrating Metabolomics with Serum Pharmacochemistry to Evaluate the Efficacy of Traditional Chinese Medicine. (February 2019) - Zhang, Ai-Hua; Sun, Hui; Yan, Guang-Li; Han, Ying; Zhao, Qi-Qi; Wang, Xi-Jun
Abstract: Evaluation of the efficacy of traditional Chinese medicines (TCMs) is an important prerequisite for discovering effective substances, lead compounds, and quality markers (Q markers). At present, there is an urgent need to develop a biological language that can act as abridge for the scientific elaboration of the efficacy of TCMs, and to further highlight the significant value of TCM. Chinese medicinal syndromes and formulae are two essential parts of TCM that directly relate to its efficacy. Syndromes and formulae have been taken as the research objects. The serum pharmacochemistry of the TCM approach with metabolomics were integrated to establish an innovative chinmedomics strategy, which is able to explore syndrome biomarkers and evaluate TCM efficacy in order to discover effective substances from TCMs. A great deal of concrete work in chinmedomics has already performed to bridge the gap between Chinese and Western medicine, and to provide a powerful approach to enhance the scientific value of TCM theory and clinical practice. This article summarizes the application of chinmedomics in identifying the candidate biomarkers of a syndrome and revealing the efficacy of the related formula. We also highlight the discovery of lead compounds and Q markers from TCMs.